Atmospheric Research Over the Western North Atlantic Ocean Region and North American East Coast: A Review of Past Work and Challenges Ahead. Issue 6 (21st March 2020) - Sorooshian, Armin; Corral, Andrea F.; Braun, Rachel A.; Cairns, Brian; Crosbie, Ewan; Ferrare, Richard; Hair, Johnathan; Kleb, Mary M.; Hossein Mardi, Ali; Maring, Hal; McComiskey, Allison; Moore, Richard; et al.
Abstract: Decades of atmospheric research have focused on the Western North Atlantic Ocean (WNAO) region because of its unique location that offers accessibility for airborne and ship measurements, gradients in important atmospheric parameters, and a range of meteorological regimes leading to diverse conditions that are poorly understood. This work reviews these scientific investigations for the WNAO region, including the East Coast of North America and the island of Bermuda. Over 50 field campaigns and long‐term monitoring programs, in addition to 715 peer‐reviewed publications between 1946 and 2019, have provided a firm foundation of knowledge for these areas. Of particular importance in this region has been extensive work at the island of Bermuda that is host to important time series records of oceanic and atmospheric variables. Our review categorizes WNAO atmospheric research into eight major categories, with some studies fitting into multiple categories (relative %): aerosols (25%); gases (24%); development/validation of techniques, models, and retrievals (18%); meteorology and transport (9%); air‐sea interactions (8%); clouds/storms (8%); atmospheric deposition (7%); and aerosol‐cloud interactions (2%). Recommendations for future research are provided in the categories highlighted above. Key Points: A total of 50+ field studies and 700+ papers illustrate the complexity of atmospheric phenomena over the West North Atlantic and North American East Coast The widest body of work has been devoted to atmospheric chemistry and has characterized urban outflow and marine emissions Multidisciplinary topics such as aerosol‐cloud and air‐sea interactions have not been sufficiently addressed and warrant high priority